Communication Technician: One of the Roles of Yehonala School Public Relations in Maintaining Image - Andy Andy; Angel Purwanti (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
School is one of the institutions in transferring the balance between moral values to students in the learning process, so as to create innovations to improve the quality of institutions nationally. Yehonala School, one of the schools in Batam City that focuses on developing and shaping the characteristics of educators. Yehonala School is a National Plus based school in partnership with Cambridge University Press, and the motto is 'To Grow in Wisdom!' starting from the Play Group level, Elementary School (SD), Junior High School (SMP), High School (SMA) and Vocational High School (SMK). Yehonala School has an image as